Anemia, Growth Impairment, and Micronutrients Status in Syrian Children Aged 12–60 Months - Radhee M. Adi; Marie Koenig; Ahmad Alwan; Sami El Khatib; Jürgen Geisel; Stefan Eber; Sahar Chamaa; Rima Obeid (International Journal of Pediatrics)
Conclusion: Anemia and low height- or weight-to-age z scores are highly prevalent among Syrian preschool children. Low folate or vitamin B12 status was common, but they did not explain these conditions. Future studies may investigate whether early life multinutrient interventions may improve child growth and anemia.